Profil Emosi Akademik Siswa selama Pembelajaran Online di SMP YPM 4 Taman Sidoarjo - Zulfa Rusdiana; Prihantika Fuji Kusuma Dewi; Abdul Muhid (Universitas Kanjuruhan Malang, 2021)
Academic emotions are emotions that arise when students are in a learning situation and are directly related to activities to achieve academic achievement. This study aims to describe students' academic emotions associated with online learning during a pandemic. This research is a descriptive study with a quantitative approach. The subjects involved in this study were 307 students of SMP YPM 4 Taman, who was determined through a stratified random sampling technique. The instrument used in this study was the Academic Achievement Questionnaire developed by Pekrun. The data analysis used was descriptive and percentage analysis. The results showed that on average students tended to have positive emotions related to learning in the high category. The positive emotions described in this study include enjoyment, hope, and pride. Furthermore, the average student also showed negative emotions in the form of anger, anxiety, shame, hopelessness, and boredom in the low and medium categories.